Efeito de cobre e chumbo, metais pesados presentes na água de formação derivada da extração do petróleo da província petroleira do Urucu - Am, sobre o tambaqui, Colossoma macropomum (Curvier, 1818) - Oliveira, Christiane Patrícia Feitosa (Instituto Nacional de Pesquisas da Amazônia - INPA, 2003)
The aim of this study was to evaluate the toxicity of two heavy metais, copper and lead, on Colossoma macropomum (tambaqui), as well as to evaluate the bioconcentration and the effects of sublethal exposure on respiratory capacity, ion regulation and health. CL5o-96h was estimated for both metais. The LC5o-96h was 0.735mg/L for copper and 28.71 mg/L for lead. Based on these values, tambaqui specimens were exposed to sublethal metal concentrations of 50% of LC5o-96h for 96 hours. For copper and lead association the animais were exposed to 25% of LC50- 96h of each metal. Tambaqui exposure to copper sublethal concentration resulted in no changes of hematological parameters; exposure to lead and its association with copper caused anemia, confirmed by a decrease in the concentration of hemoglobin, hematocrit, and the number of red cells. Plasma Na"^ were reduced in the copper exposed group and the inverse occurred for lead the exposed group. The leveis decreased in copper and increased in animais exposed to lead and lead + copper association. Leveis of Cl" increased in lead and lead + copper exposed animais. Based on these resuits we concluded that copper and lead directiy affect ion regulation. Plasma glucose increased in the animais exposed to copper; however, plasma lactate decreased in this group suggesting that, despite the stress, the anaerobic metabolism of these animais showed no changes. Exposure to these heavy metais caused serious hepatic damage, evidenced by high alanine and aspartate aminotransferase and alkaline phosphatase enzyme concentration. Increased cholinesterase leveis in animais exposed to lead and lead + copper suggest nervous disturbances. The exposure to sublethal metal concentration caused no changes in TBARS plasma leveis. However, erithrocitic nuclear abnormality was increased in animais exposed to sublethal copper concentration. Copper increased in gilis and liver and lead increased in the gilis of animais exposed to sublethal concentrations. The exposure of C. macropomum to copper and lead sublethal concentrations promoted serious physiological and biochemical disturbances compromising the health of this fish species.
Keywords: Peixes - intoxicação - Cobre e Chumbo; Colossoma macropomum; Toxicologia - Peixes